Twenty-year follow-up of 160 patients with ataxia-telangiectasia - Ersoy, Fügen; Berkel, A. İzzet and Sanal, Özden and Oktay, Hamiyet (The Turkish Journal of Pediatrics, 1991)
The clinical and immunological findings of 160 patients diagnosed over a period of twenty years as having ataxia-telangiectasia (AT) are presented. The study group composed of 68 females and 92 males were members of 117 families. The rate of parental consanguinity was 65 percent. The incidence of AT in 117 families was 36.6 percent. All patients had the characteristic facial and postural features of AT. The mean duration of follow-up of 160 patients was 6.35 years. Fifty patients had died during the follow-up (36 of pulmonary infections, 14 of malignancies). Somatic growth retardation was a prominent feature. Recurrent sinopulmonary infections were detected in 66 percent of patients. Two patients had hypothyroidism, one had diabetes mellitus, and one had both conditions. The incidence of malignancies was found to be 2.3 percent in the immediate relatives of the patients. The total lymphocyte count was low in 57 percent, and skin tests to PHA, candida, PPD and SK-SD were negative in 17.7%, 72.6%, 43.6%, and 78.2% of patients, respectively. In vitro blastogenic response to PHA was low in 61 percent of patients. The mean value of E-rosette formation was significantly lower than control values. Six patients had low serum IgG levels. The serum IgM level was high in 26.6 percent of patients and the IgA level was low or absent in 51.3 percent. There was no correlation between immune disturbance and duration of illness.